Helicobacter pylori CagL Activates ADAM17 to Induce Repression of the Gastric H, K-ATPase α Subunit - Saha, Arindam; Backert, Steffen; Hammond, Charles E.; Gooz, Monika; Smolka, Adam J. (Gastroenterology, 2010)
Background & Aims: Infection with Helicobacter pylori represses expression of the gastric H, K-adenosine triphosphatase α-subunit (HKα), which could contribute to transient hypochlorhydria. CagL, a pilus protein component of the H pylori type IV secretion system, binds to the integrin α5β1 to mediate translocation of virulence factors into the host cell and initiate signaling. α5β1 binds a disintegrin and metalloprotease (ADAM) 17, a metalloenzyme that catalyzes ectodomain shedding of receptor tyrosine kinase ligands. We investigated whether H pylori-induced repression of HKα is mediated by CagL activation of ADAM17 and release of heparin-binding epidermal growth factor (HB-EGF). Methods: HKα promoter and ADAM17 activity were measured in AGS gastric epithelial cells transfected with HKα promoter-reporter constructs or ADAM17-specific small interfering RNAs and infected with H pylori. HB-EGF secretion was measured by enzyme-linked immunosorbent assay analysis, and ADAM17 interaction with integrins was investigated by coimmunoprecipitation analyses. Results: Infection of AGS cells with wild-type H pylori or an H pylori cagL-deficient isogenic mutant that also contained a wild-type version of cagL (P12ΔcagL/cagL) repressed HKα promoter-Luc reporter activity and stimulated ADAM17 activity. Both responses were inhibited by point mutations in the nuclear factor-κB binding site of HKα or by infection with P12ΔcagL. Small interfering RNA-mediated silencing of ADAM17 in AGS cells inhibited the repression of wild-type HKα promoter and reduced ADAM17 activity and HB-EGF production, compared to controls. Coimmunoprecipitation studies of AGS lysates showed that wild-type H pylori disrupted ADAM17-α5β1 complexes. Conclusions: During acute H pylori infection, CagL dissociates ADAM17 from the integrin α5β1 and activates ADAM17-dependent, nuclear factor-κB-mediated repression of HKα. This might contribute to transient hypochlorhydria in patients with H pylori infection. © 2010 AGA Institute.
Created from Fastlane, Scopus look-up
Keywords: ADAM17; CagL; H; K-ATPase; Helicobacter pylori